The impact of external shocks on the comparative advantage of the Malaysian food processing industry. - Ismail, Mohd Mansor; Sidique, Shaufique Fahmi; Radam, Alias (Faculty of Economics and Management, Universiti Putra Malaysia., 2008)
Scheduled liberalization of trade preferences under the World Trade Organisation and the Asean Free Trade Area has heightened the challenges faced by the Malaysian food producers. To penetrate a wider range of markets, Malaysian food processors have to identify food sub-sectors that are internationally competitive. These sub-sectors should not only withstand internal shocks but also external shocks such as the financial crisis in 1997. This article examines the levels of benefit-cost ratios for various productions of food products to analyze the comparative advantages before and after the 1997 financial crisis. The competitiveness of the food processing industry in Malaysia was determined using the Domestic Resource Cost (DRC) method. Twenty food sectors were assessed using the Malaysian food production and trade data from 1985 to 2001. Processed foods with a high comparative advantage sustained after the crisis can be considered as viable to compete with foreign products in domestic and overseas markets. Meat products in import substitutions, palm oil, kernel oil, sago and tapioca, and cocoa in traditional exports and fish products in emerging exports are examples of food sub-sectors that are gaining competitiveness in the post crisis period.